A novel drug that reduces pneumococcal toxicity by targeting pneumolysin (PLY): efficacy of the traditional Chinese medicine Radix Paeoniae Alba - Xu, Yan; Han, Jing; Zhou, Yonglin; Sun, Liping (Frontiers in Pharmacology, 2025)
ObjectiveWhile existing virulence-targeting strategies predominantly rely on single-component inhibitors that exert evolutionary pressure, this study pioneers an innovative approach using the multicomponent traditional Chinese medicine Radix Paeoniae Alba (RPA). Unlike conventional monotherapeutic agents, RPA uniquely inhibits pneumolysin (PLY) oligomerization without affecting bacterial growth, thereby circumventing resistance development—a critical limitation of current therapies. We aimed to elucidate the novel mechanism by which RPA attenuates Streptococcus pneumoniae pathogenicity by inhibiting the pore-forming activity of PLY while preserving host microbiota homeostasis according to the holistic TCM philosophy.MethodsUsing a murine pneumococcal infection model, we evaluated the therapeutic effects of RPA on lung inflammation. Hemolysis assays and A549 cell viability tests were performed to assess PLY inhibition. Western blotting was used to characterize the PLY oligomerization dynamics following RPA treatment. Bacterial growth curves confirmed the nonantibacterial nature of RPA.ResultsRPA significantly reduced pulmonary inflammation (p < 0.05) and the levels of inflammatory cytokines (IL-1β, IL-6, and TNF-α) without altering S. pneumoniae growth. Mechanistically, RPA inhibited PLY oligomerization (64 μg/mL) in a dose-dependent manner, thereby preventing erythrocyte hemolysis and alveolar epithelial damage.ConclusionThis study provides the first evidence that a multicomponent TCM achieves targeted antivirulence effects by blocking PLY oligomerization, providing a resistance-proof therapeutic strategy. Our findings bridge the “body-strengthening and evil-eliminating” principle of TCM with molecular pathogenesis, highlighting the potential of RPA as a novel antivirulence agent for pneumococcal infections.